Aplikasi Metode Volumetrik dalam Estimasi Potensi Panas Bumi Berdasarkan Parameter Fisis Reservoir (Studi Kasus Daerah Panas Bumi “Z”) - Latifah Nurul Qomariyatuzzamzami; Zuhdiyah Matienatul Iemaaniah; Alamta Singarimbun (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2023)
Geothermal is a renewable energy strategically developed in Indonesia, but its utilization has not been maximized. Geothermal exploration requires high costs, so estimating energy reserves in potential areas is essential. This study was conducted to determine the electrical energy potential of geothermal area "Z" by volumetric method and determine the influence of saturation, porosity, and length of generation time on the potential of geothermal electrical energy. The volumetric method used is the lumped parameter model. The calculation was carried out with variations in water saturation 0% - 80%, rock porosity 10% - 40%, and the length of generation time 25 - 40 years. The highest estimated electrical energy of geothermal area "Z" is 188 MWe obtained at 80% water saturation, 10% porosity, and 25 years generation duration, while the lowest is 80 MWe obtained with 0% water saturation, 40% porosity, and 40 years of generation duration. At the same porosity, the greater the water saturation, the greater the value of geothermal electricity reserves of the area "Z." The greater the porosity, the greater the effect of increasing water saturation on increasing electrical energy reserves. The large porosity of rocks causes their energy to be smaller since the heat dominance of geothermal regions "Z" is given by the heat of rocks. The length of generation time affects the amount of geothermal electrical energy, that is, the longer the production time, the smaller the reserve.